2021
DOI: 10.1155/2021/9536054
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Etoricoxib following Third Molar Surgery: A Meta-analysis

Abstract: Background. The purpose of this meta-analysis was to assess the clinical efficacy of etoricoxib in comparison with traditional NSAIDs for postoperative pain after third molar surgery. Methods. The quality of studies found in PubMed and Google Scholar was evaluated with Cochrane Collaboration’s risk of bias tool. Data on total consumption of rescue analgesics, number of patients using rescue analgesics, global assessment of study treatments, and adverse effects were extracted exclusively from high-quality clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…On the other hand, the NIME presents its maximum concentration from 1.22 to 2.75 h (Singla et al, 2000), reaching 3 h (Hanif et al, 2017). Similar findings were described by other studies (Costa et al, 2015; la Torre et al, 2021). In a meta‐analysis of clinical trials on preemptive analgesia of third molar surgeries, no significant difference in the amount of rescue medication was observed (Moore et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the NIME presents its maximum concentration from 1.22 to 2.75 h (Singla et al, 2000), reaching 3 h (Hanif et al, 2017). Similar findings were described by other studies (Costa et al, 2015; la Torre et al, 2021). In a meta‐analysis of clinical trials on preemptive analgesia of third molar surgeries, no significant difference in the amount of rescue medication was observed (Moore et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported by Isiordia-Espinoza et al, 2022 on the safety profile of celecoxib in comparison to active controls following third molar surgery [ 35 ]. Another meta-analysis found no difference in adverse events (nausea, vomiting, dizziness, headache, and alveolar osteitis) between etoricoxib and traditional NSAIDs in a third molar surgery [ 58 ]. A similar risk of adverse effects has been reported between celecoxib and traditional NSAIDs with respect to gastrointestinal and vascular effects and acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of gastrointestinal adverse effects was higher with diclofenac than with etoricoxib in patients with osteoarthritis. Finally, there is no evidence of serious adverse effects with the use of etoricoxib [ 58 ]. Our research team recommends increasing the number of clinical trials that test COX-2 selective agents in periodontal surgery to confirm their analgesic and anti-inflammatory efficacy, also considering the reporting of adverse effects essential, which will allow us to determine if there is a larger susceptible population.…”
Section: Discussionmentioning
confidence: 99%
“…Etoricoxib (ETO) is considered a selective cyclo-oxygenase-2 inhibitor, a sub-class of non-steroidal anti-inflammatory drugs, that obstructs prostaglandin production by inhibiting cyclo-oxygenase enzymes, thus reducing pain, discomfort, and inflammation resulting in an analgesia effect (Ahmadi et al., 2022 ; Farag & Bahra, 2022 ; Ju et al., 2022 ). Multiple clinical trials have demonstrated the clinical efficacy of ETO in treating acute and chronic pain associated with different diseases like acute gout, dysmenorrhea, oral surgery, rheumatoid arthritis, osteoarthritis, and chronic lower back pain (la Torre et al., 2021 ). The assessment of its side effects showed some cardiovascular risks, different renal events, dizziness, headache, and GIT disturbances like nausea, vomiting, and peptic ulcer (Kirschneck et al., 2019 ; la Torre et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%